2000
DOI: 10.1524/ract.2000.88.9-11.729
|View full text |Cite
|
Sign up to set email alerts
|

The partitioning of uranium and neptunium onto hydrothermally altered concrete

Abstract: SummaryPartition coefficients (K d ) of U(VI) and Np(V) on untreated and hydrothermally altered concrete were measured in 0.01 M NaCl and 0.01 M NaHCO 3 solutions as functions of concentration of the radionuclides, pH, and time. The partition coefficients for both U(VI) and Np(V) on hydrothermally altered concrete are significantly lower than those on untreated concrete. The partition of both U(VI) and Np(V) are pH dependent, although the pH dependence does not necessarily reflect precipitation of U and Np-bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 18 publications
2
26
0
2
Order By: Relevance
“…EXAFS studies on U(VI)-loaded untreated and hydrothermally treated HCP samples further revealed preservation of the UO 2 2+ moiety in all samples, indicating that the +VI redox state was stable [5,6]. Samples with U(VI)-sorbed onto hydrothermally altered concrete also suggested cluster formation or surface precipitation as indicated by the presence of U−U backscattering contributions in the EXAFS spectra [6].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…EXAFS studies on U(VI)-loaded untreated and hydrothermally treated HCP samples further revealed preservation of the UO 2 2+ moiety in all samples, indicating that the +VI redox state was stable [5,6]. Samples with U(VI)-sorbed onto hydrothermally altered concrete also suggested cluster formation or surface precipitation as indicated by the presence of U−U backscattering contributions in the EXAFS spectra [6].…”
Section: Introductionmentioning
confidence: 86%
“…Samples with U(VI)-sorbed onto hydrothermally altered concrete also suggested cluster formation or surface precipitation as indicated by the presence of U−U backscattering contributions in the EXAFS spectra [6]. The chemical nature of the U(VI) species immobilized in HCP has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…65 These researchers used XANES absorption edge determinations and the degree of "axial" O bonding from the EXAFS to estimate the amount of Np(V). They reported that most of the Np(V) reduced over time in the solution or concrete slurries that had pH values of 9.3 through 12.3.…”
Section: Characteriza Tion Of Np On Surfaces With Xafsmentioning
confidence: 99%
“…Although X-ray absorption fine structure (XAFS) spectroscopy has become an increasingly important tool for investigating immobilization processes in cementitious systems (e.g., [14][15][16][17][18][19][20][21][22][23][24][25][26]), very few studies have used XAFS to develop a molecular-level understanding of the U(VI) uptake by cementitious materials [27,28]. In these studies the coordination environment of U(VI)-doped untreated and hydrothermally treated concrete was probed in the alkaline pH range (pH 9-12).…”
Section: Introductionmentioning
confidence: 99%